Operational risk management in financial institutions: A literature review - Suren Pakhchanyan (International Journal of Financial Studies, 2016)
Following the three-pillar structure of the Basel II/III framework, the article categorises and surveys 279 academic papers on operational risk in financial institutions, covering the period from 1998 to 2014. In doing so, different lines of both theoretical and empirical directions for research are identified. In addition, this study provides an overview of existing consortia databases and other publicly available sources on operational loss that may be incorporated into empirical research, as well as in risk measurement processes by financial institutions. Finally, this paper highlights the research gaps in operational risk and outlines recommendations for further research.
Keywords: G00; G20; G32; 330; Basel framework; operational risk; risk management; risk indicators